2022
DOI: 10.9734/ajeba/2022/v22i1830650
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Internal Labour Migration from Agriculture Sector to Non-agricultural Sector in Bangladesh: An Empirical Analysis

Abstract: Aims: In past, labour was extensively used in agriculture sector and there was huge surplus labour in agriculture sector. However, such trend has recently been changed where surplus labour in agricultural sector has reduced significantly and agriculture sector compete with non-agricultural sector in terms of hiring labour. Thus, the present study was undertaken to analyze the determinants of labour migration from agriculture sector to non-agricultural sector in Gopalganj district of Bangladesh. Place and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In this study, oversubscription reported an average frequency of 2.56 times, a minimum of 0.01 times and a maximum of 17.46 times, demonstrating a wide difference between the minimum and maximum frequency. The average oversubscription is lower than reported for other countries, such as Bangladesh with an average of 20.20 times and Malaysia with an average of 30.45 times (Rahman et al , 2017; Tajuddin et al , 2015). Nevertheless, Pakistan's low oversubscription between 2000 and 2017 prescribes that IPOs with the lowest demand tends to attract more investors since these IPOs were traded below the offer price before the aftermarket.…”
Section: Empirical Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, oversubscription reported an average frequency of 2.56 times, a minimum of 0.01 times and a maximum of 17.46 times, demonstrating a wide difference between the minimum and maximum frequency. The average oversubscription is lower than reported for other countries, such as Bangladesh with an average of 20.20 times and Malaysia with an average of 30.45 times (Rahman et al , 2017; Tajuddin et al , 2015). Nevertheless, Pakistan's low oversubscription between 2000 and 2017 prescribes that IPOs with the lowest demand tends to attract more investors since these IPOs were traded below the offer price before the aftermarket.…”
Section: Empirical Results and Discussionmentioning
confidence: 64%
“…DPA is dummy of premium offered which is display as without premium 0 and with premium 1, DFC is dummy of crisis period which shows listed IPO during crisis period 0, other than crisis period 1. DPM is a dummy of pricing mechanism IPO offered with fixed price 1, otherwise with book building 0 Bangladesh with an average of 20.20 times and Malaysia with an average of 30.45 times (Rahman et al, 2017;Tajuddin et al, 2015). Nevertheless, Pakistan's low oversubscription between 2000 and 2017 prescribes that IPOs with the lowest demand tends to attract more investors since these IPOs were traded below the offer price before the aftermarket.…”
Section: Ipo Initial Return In Pakistanmentioning
confidence: 99%
“…(2019), where the authors reported an average investor demand of 33.59 times and 36.62 times, respectively. Furthermore, Malaysia has a relatively higher average subscription level as compared to other emerging economies like Bangladesh of 20.20 times (Rahman et al. , 2017), Pakistan of 2.52 times (Mehmood and Mohd-Rashid, 2020) and India of 10.28 (Arora and Singh, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the current study reports an average investor demand of 25.15 times, which is significantly lower than the findings of other studies such as Low and Yong (2011) and Albada et al (2019), where the authors reported an average investor demand of 33.59 times and 36.62 times, respectively. Furthermore, Malaysia has a relatively higher average subscription level as compared to other emerging economies like Bangladesh of 20.20 times (Rahman et al, 2017), Pakistan of 2.52 times (Mehmood and Mohd-Rashid, 2020) and India of 10.28 (Arora and Singh, 2020). In accordance with Chowdhry and Sherman's (1996) model, fixed-price regime issues are characterised by extreme OSRs in comparison to book-building issues, which is attributable to the high level of uncertainty.…”
Section: Descriptive Statisticsmentioning
confidence: 91%
“…This study's findings will aid regulators in strengthening Bangladesh's stock market by guiding their course of action. According to the research (Rahman, Hossain, and Omar, 2017), market lot has a large positive effect on IPO subscription times, however EPS and offer price have a considerable negative influence. Figure 1 shows the various factor that determine the performance of IPO.…”
Section: Literature Reviewmentioning
confidence: 99%